Substituição do azodicarbonamida (ADA) na produção de pão francês: avaliação de reagentes alternativos por planejamento fatorial - Carvalho, Patricia Aparecida Pilegi de Almeida (Universidade Federal de São Carlos, 2025)
In Brazil, French-style bread/roll is a food consumed daily, but despite its popularity, many people are unaware of the challenges faced by the industry in maintaining consistent product quality, regardless of variations in industrial processes or fluctuations in wheat flour quality, especially during periods of wheat crop changes. Given this scenario, industries use food-grade chemical additives in the production of French-style bread/roll, which allows the product to maintain the expected standards of texture and physical characteristics such as volume, crust cracking, and “eyelash” (the typical split on top) demanded by consumers. Azodicarbonamide (ADA) is a chemical compound used in French-style bread/roll production, but its use is restricted or banned in some countries, mainly due to its potential toxicity to workers who handle bread and related products. In Brazil, the use of ADA is permitted within the limits established by Anvisa (the Brazilian Health Regulatory Agency). However, identifying ingredients and processing aids that can replace this reagent without major impacts on cost, processing, quality, and especially on the sensory and physical characteristics of French-style bread/roll is crucial. Therefore, the use of chemometric tools related to Design of Experiments (DoE) and exploratory data analysis becomes an important approach for evaluating potential ADA substitutes. In this way, this master’s thesis aimed to replace ADA in French-style bread/roll production by applying chemometric tools for the screening and selection of sustainable ingredients and processing aids. Thus, contributing to the development of a solution closer to a clean-label principles and suitable for industrial use, supporting the availability of healthier bread alternatives for consumers. The data were obtained through laser topography measurements of the breads (Volscan), as well as through the measurement of the rheological interactions between the ingredient and/or processing aid and wheat flour using Alveograph, Mixolab, and Rheofermentometer methods.
Substitution of azodicarbonamide (ADA) in Brazilian french-style bread/roll manufacturing: assessment of alternative agents via factorial experimental design
Keywords: Plackett & Burman; PB; Central Composite Design; CCD; Planejamento de Experimentos; DoE; Pão Francês; Azodicarbonamida; Enzimas; Aditivos; Farinha de trigo; Reologia; Mixolab; Alveógrafo; Reofermentômetro; Análise Sensorial; Design of Experiment; French-style bread/roll; Azodicarbonamide; Enzymes; Additives; Wheat Flour; Rheology; Sensory analysis; Alveograph; Rheofermentometer; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA; 12. Consumo e Produção Responsáveis; 3. Saúde e Bem-Estar